Hubungan Asupan Protein Dengan Kadar Ureum, Kreatinin, dan Kadar Hemoglobin Darah pada Penderita Gagal Ginjal Kronik Hemodialisa Rawat Jalan Di RS Tugurejo Semarang - Nura Ma’shumah; Sufiati Bintanah; Erma Handarsari (Jurnal Gizi, 2014)
Chronic renal failure or end-stage renal disease is a progressive destruction of kidney structure and continuously. Renal function that can not be recovered where the body's ability to maintain metabolic balance, and fluid electrolyte failure, which led to uremia (Elizabeth, 2009). The purpose of this study was to determine the "Relationship with Protein Intake Levels of urea, creatinine and Hb Levels in Patients with Chronic Renal Failure in the Outpatient Hemodialysis Tugurejo Hospital Semarang" This type of research is Clinical Nutrition descriptive analytic with cross sectional approach. Population in this study were all out patients with chronic renal failure undergoing hemodialysis at Tugurejo Hospital, Semarang. The research was done at June-July 2013. the criteria of patient are had urea levels> 40 g / dl and creatinine levels > 1.3 g /dl, able to communicate, aged 17 years old and above, we gained the sample as many as 35 pasient.  To collecting the data, we used interview  with food frequency tools. To test the correlation between protein intake and levels of urea, creatinin, blood hemoglobin level, we  used the Rank Spearman test and  to tested  the normality of data we used the kolmogorov-smirnov test The results showed that there are 21 (60,0%)  patients with kidney failure are  male  more than female. The  aged of 41-60 years old are  17 pasient  (48.6%), pasient with  normal nutritional status are 17 people (48.6%).  The average of protein intake is 80,02 gram per day. All of patient (100%) have  blood urea levels over than the normal level. and the blood creatinine levels likewise all of patient ,  men (20 patient) and  women (14 patient) have blood Hb level  in the category entirely lacking. Statistical test result showed that there are  a corelation between protein intake with the levels of urea (p value 0,019 <0,05),  protein intake with the level of  kreatinin (p value 0,044<0,05), and protein intake with the Hb levels (p value 0,024< 0,05)